Enabling Nature-Based Solutions to Build Back Better—An Environmental Regulatory Impact Analysis of Green Infrastructure in Ontario, Canada - Vidya Anderson; William A. Gough (Buildings, 2022)
The application of green infrastructure in the built environment delivers a nature-based solution to address the impacts of climate change. This study presents a qualitative evidence synthesis that evaluates policy instruments which enable the use and implementation of green infrastructure, using Ontario, Canada as a case study. Unpacking the elements of the policy landscape that govern green infrastructure through environmental regulatory impact analysis can inform effective implementation of this nature-based solution and support decision-making in public policy. This environmental regulatory impact analysis is based on a systematic review of existing policy instruments, contextual framing in a continuum of coercion, and identification of alignment with relevant UN SDGs. Enabling widespread usage of green infrastructure in the built environment could be a viable strategy to build back better, localize the UN SDGs, and address multiple climate change impacts.